The Importance of Human Capital in the Life of a Corporation: the Influence of Managers on the Dynamics of the Social Environment - E. A. Kamyshina (Дискурс)
Introduction. The purpose of the article is to analyze the influence of managers and their human capital on the corporate social environment, offering tools for such analysis and studying the factors of human capital formation. The relevance of the work is determined by the practical application of network research methods using the in-depth interview method. The result of using such methods is the analysis of the qualities of managers that influence the building of the most positive socio-structural relations in the corporation and contribute to the development of the human capital of the corporation, which is important for society.Methodology and sources. In developing the methodology there were used the works of sociologists devoted to values (M. Weber, T. Parsons, F. Tennis, P. Bourdieu, V.A. Yadov) and the theory of network human capital (P.P. Deryugin, S.A. Kravchenko, S.A. Dyatlov) were used. The results of research by N.E. Tikhonova, S.A. Solntsev, M. Goltzman and others on the role of leaders in Russian society were used. In addition to the in-depth interview method, the research methodology was based on the concept of "Management Grid", which reveals the work style of a manager through his self-assessment.Results and discussion. This article is an applied research that reveals the role of human capital of managers in the life of a corporation and its impact on the social environment. It confirms the key importance of human capital and the social institution of corporations for the formation of social structure and economic development, and offers practical recommendations for corporate management with an emphasis on the development of human capital. Conclusion. The human capital of managers significantly affects the interaction inside and outside the corporation and the social dynamics of society as a whole. The development of leadership competencies, skills and values plays a key role for the success of corporations and society as a whole. The social component of the life activity of corporations is focused on production by meeting social needs, which emphasizes the central importance of human capital and its impact on the social structure of society.